Math, asked by tantyshashi, 10 days ago

factorise m^2n^2 + m^2 + n^2 +1​

Answers

Answered by shreekrishna35pdv8u8
1

Step-by-step explanation:

 {m}^{2}  {n}^{2}  +  {m}^{2}  +  {n}^{2}  + 1 \\  =  {m}^{2} ( { {n}^{2} }  + 1) + 1( {n}^{2}  + 1) \\  = ( {n}^{2}  + 1)( {m}^{2}  + 1)

Answered by diwanamrmznu
2

EVALUETION★

given★

m {}^{2}n {}^{2} + m {}^{2}  + n {}^{2}  + 1

we take common

m {}^{2}  \:.  \: 1

in equetion

 =  m {}^{2} (n {}^{2}  + 1) + 1(n {}^{2}  + 1)

we see that two

n {}^{2} + 1

common so this written only one

here your answer

 = (m {}^{2}  + 1)(n {}^{2}  + 1)

==========================================

I hope it helps you

Similar questions